Drift - Delfino, Annmarie, author; Dungy, Camille, advisor; Beachy-Quick, Dan, advisor; Lehene, Marius, committee member (Colorado State University. Libraries, 2022)
The poems in Drift explore cyclical, nonlinear ways of experiencing and viewing time and our relationship to the natural world. Centered in the coastal landscapes of Southern California, these poems examine how ecology shifts over time. Interspersed throughout the collection are poems from the point of view of a young speaker as she revisits her childhood memories, connects them to the present day, and imagines how her present self might evolve in the future. Both the landscape-centered and human-centered poems question what appears stable and fixed, exploring the ways memory and landscape are malleable, fluid, and interconnected.